Discourses on Society
XV, 386 p. 1 illus.
Keywords: This book, which represents probably the most comprehensive discussion of the emergence of modem social science yet produced, is of far more than merely historical interest. The contributors set out to rewrite the history of the social sciences and to show the limitations of conventional conceptions of their development. These tasks they accomplish with great success and much distinction. Yet in so doing they contribute in a direct way to our understanding of the relation between social analysis and the nature of human societies today. The brilliant and distinctive perspective of the papers in this collection is to demonstrate, with many specific examples, that social science and modem institutions have helped shape each other in mutual interplay. Modem systems are in some part con stituted through the reflexive incorporation of developing social science knowledge; on the other hand, the social sciences organise themselves in terms of a continuing reflection upon the evolution of those systems. Such a perspective, as Wagner and Wittrock in particular make clear, does not in any way either impugn the status of knowledge claims made within social science or destroy the independent reality of social institutions. The book questions the notion that the institutionalising of the social sciences can be understood as a process of their increasing autonomy from extemal social connections. 'Autonomy' forms a mode of legitima tion and a basis of power rather than a distinctive phenomenon as such.